Isopods infesting Atlantic bonefish (Albula vulpes) host novel viruses, including reoviruses related to global pathogens, and opportunistically feed on humans - Tony L. Goldberg; Addiel U. Perez; Lewis J. Campbell (Parasitology)
Isopods infest fish worldwide, but their role as disease vectors remains poorly understood. Here, we describe infestation of Atlantic bonefish (Albula vulpes) in Belize with isopods in two of three locations studied, with infestation rates of 15 and 44%. Isopods fed aggressively, and infested fish showed missing scales and scars. Gross morphologic and molecular phylogenetic analyses revealed the isopods to cluster within the family Aegidae and to be most closely related to members of the genus Rocinela, which are globally distributed micro-predators of fish. Metagenomic analysis of 10 isopods identified 11 viruses, including two novel reoviruses (Reovirales) in the families Sedoreoviridae and Spinareoviridae. The novel sedoreovirus clustered phylogenetically within an invertebrate-specific clade of viruses related to the genus Orbivirus, which contains arboviruses of global concern for mammal health. The novel spinareovirus clustered within the fish-infecting genus Aquareovirus, which contains viruses of global concern for fish health. Metagenomic analyses revealed no evidence of infection of bonefish with the novel aquareovirus, suggesting that viremia in bonefish is absent, low, or transient, or that isopods may have acquired the virus from other fish. During field collections, isopods aggressively bit humans, and blood meal analysis confirmed that isopods had fed on bonefish, other fish, and humans. Vector-borne transmission may be an underappreciated mechanism for aquareovirus transmission and for virus host switching between fish and other species, which has been inferred across viral families from studies of deep virus evolution.